PEMBUATAN MI SINGKONG : KARAKTERISASI MI SINGKONG HASIL PENAMBAHAN JENIS PROTEIN DAN RASIO TEPUNG SINGKONG TERHADAP TAPIOKA - Hardoko Hardoko; Clara Tasia; Titri Siratantri Mastuti (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2021)
Cassava noodles are noodles made from cassava and do not contain gluten (non gluten). Non-gluten-based noodles are less attractive to the public because of the physical properties of the noodles. The purpose of this study was to obtain the appropriate type of protein and the ratio of cassava flour to tapioca in the manufacture of cassava noodles. The method used is an experimental method which is divided into two stages. The first stage of the research was made treatment of soy protein isolate (ISP) 5%, ISP 10%, eggs 2.5%, 5%, and 7.5%. The second stage was treated with the ratio of cassava flour - tapioca ((80:20, 70:30, 60:40, 50:50) and the best types of protein were stage one (X), X-1.5%, and X + 1.5%. that the addition of 5% eggs can reduce the value of cooking losses, stickiness level, and increase the water absorption and the elasticity of the noodles The results of the sensory comparison test with commercial noodles show that cassava noodles are more chewy and stickier than commercial noodles but have no taste and aroma of cassava. In the comparison test between cassava noodles and commercial noodles, the value is acceptable. The results of the second stage of the study showed that the best noodles were the best cassava noodles from the treatment of the ratio of 60:40 cassava flour: tapioca and the addition of eggs of 6.5%. This treatment resulted in shrunken cassava noodles. lower cooking and stickiness, high water absorption, high elasticity, and sensoy hedonic grades are somewhat preferred.